PERAN KOMITE MADRASAH DALAM MEMBANTU MENGEMBANGKAN SARANA PRASARANA DI MADRASAH ALIYAH NEGERI 2 PAMEKASAN - Laily Mutohharoh (re-JIEM (Research Journal of Islamic Education Management), 2021)
In educational units such as madrasas, the existence of madrasa committees is very important. Whether its role has a big impact or not, this independent institution plays a very important role in improving the quality of services by providing consideration, direction, and support for personnel, facilities, and infrastructure as well as supervision at the level of the education unit. This study aims to describe the role of the madrasah committee in helping to develop infrastructure at MAN 2 Pamekasan, with sub-focuses including (1) the concept of infrastructure development, (2) the implementation of infrastructure development, (3) the implications of infrastructure development, carried out at Madrasah Aliyah Negeri 2 Pamekasan. This research uses a qualitative approach with the type of case study. The results of this study indicate that: 1) the concept of infrastructure development is carried out by setting goals in advance and making a madrasa committee work program, 2) the implementation of infrastructure development is carried out with the madrasa committee acting as a giver of consideration, as a supporter, as a controller and as a mediator, 3) The perceived implication of the development of infrastructure facilities is the increasing number of infrastructure facilities owned by madrasas which are now by the standardization of infrastructure facilities that have been determined.